2020
DOI: 10.1007/s10198-020-01205-9
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of methods for obtaining 0 = dead anchors for latent scale EQ-5D-Y values

Abstract: Objectives Discrete choice experiments (DCEs) can be used to obtain latent scale values for the EQ-5D-Y, but these require anchoring at 0 = dead to meet the conventions of quality-adjusted life year (QALY) estimation. The primary aim of this study is to compare four preference elicitation methods for obtaining anchors for latent scale EQ-5D-Y values. Methods Four methods were tested: visual analogue scale (VAS), DCE (with a duration attribute), lag-time time trade-off (TTO) and the location-of-dead (LOD) appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 29 publications
6
61
4
Order By: Relevance
“…Higher values were placed on health states by children when compared with values placed on health states by adults. This tendency was also reported by Shah et al 9 These studies confirmed the necessity to develop EQ-5D-Y value sets and that, in this respect, the application of adult value sets was not appropriate.…”
supporting
confidence: 77%
“…Higher values were placed on health states by children when compared with values placed on health states by adults. This tendency was also reported by Shah et al 9 These studies confirmed the necessity to develop EQ-5D-Y value sets and that, in this respect, the application of adult value sets was not appropriate.…”
supporting
confidence: 77%
“…It is important to note that an additional set of data would be required to “anchor” these DCE data onto the QALY scale. 33 , 34 It is not necessarily the case that the anchoring task would be feasible in a sample of adolescents, especially if an approach such as time tradeoff is used, as in the EQ-5D-Y-3L protocol. 6 If it were feasible, it would theoretically be possible to generate an EQ-5D-Y-3L value set based entirely on adolescent preferences, which could be used in evaluations of interventions aimed at younger populations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large volume of work has been carried out with the purpose of addressing this anchoring problem. See for instance [18][19][20][21][22][23] for examples of this work. Until this anchoring problem is properly resolved, DCE cannot be an alternative to the TTO approach, but DCE data may add extra information to produce a better model for valuation data.…”
Section: Introductionmentioning
confidence: 99%